INFLUENCE OF TECHNOLOGY LEADERSHIP AND USE OF INFORMATION AND COMMUNICATION TECHNOLOGY IN SCHOOLS: ONE ANALYSIS - Mohd Helmee Firdaus Salehudin (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
eadership has a positive relationship in the performance of an organization with significant impact in influencing individuals and organizations achieve effectiveness. In line with the implementation and integration of the use of information and communication technology (ICT) in schools, school leadership role very important in implementing the agenda the Ministry of education (MOE) to answer the development of ICT in the globalization. Nevertheless, analysis of the findings of several studies have shown the use of computers in Volume: 1 Issues: 2 [December, 2016] pp.17-23] International Journal of Education, Psychology and Counseling eISSN: 0128-164X Journal homepage: www.ijepc.com18 schools Malaysia still stood at a low level and medium level achievement in vision and leadership in the implementation of ICT in schools. Therefore, the approach to technology leadership are needed to establish the effectiveness of ICT integration in school. Approach to leadership competency ICT technology to create school leaders self in order to lead effectively and provide their school to face the future.